Clinical Efficacy of Neurotropin for Lumbar Spinal Stenosis with Low Back Pain - Yawara Eguchi; Yasuchika Aoki; Masaomi Yamashita; Kazuki Fujimoto; Takashi Sato; Koki Abe; Masashi Sato; Hajime Yamanaka; Toru Toyoguchi; Keisuke Shimizu; Sumihisa Orita; Kazuhide Inage; et al. (Pain and Therapy, 2023)
Abstract Purpose We compared the clinical effects of Neurotropin, limaprost alfadex, and a combination of both drugs for lumbar spinal stenosis (LSS) with low back pain (LBP). Methods We conducted a multicenter, randomized, active-controlled, open-label trial from March 2021 to May 2022. Participants were patients diagnosed with LSS by MRI and were randomly assigned to three groups: Neurotropin/limaprost combination (NL group), Neurotropin (N group), and limaprost group (L group). Participants received the drugs administered orally for 12 weeks, and each examination and observation was performed before any drug administration and every 2 weeks thereafter. We recorded age, sex, height, weight, duration of symptoms, intermittent claudication distance, level of stenosis in MRI, and concomitant analgesics as examination items in the trial period. Items measured during the trial were visual analog scale (VAS) score (mm) for LBP, leg pain and numbness, walking activity (walking speed, stride length), standing balance (3 m Timed Up-and-Go (TUG) Test results, Five Times Sit-to-Stand Test (FTSST) results), LBP/Quality of Life (QOL)-related scores (Oswestry Disability Index (ODI), Euro QOL 5-Dimensions 5-Level (EQ-5D-5L), Roland–Morris Disability Questionnaire (RDQ)), psychological factors (Pain catastrophizing scale (PCS) and Pain Self-Efficacy Questionnaire (PSEQ) scores), and adverse events. Each item was evaluated using changes at each visit (weeks 2–12) from baseline value before drug administration (week 0), and changes were considered significant when p < 0.05. Results We included results from 64 patients in the present study; 24 were assigned to the NL group (mean age 71.2 years), 20 to the N group (mean age 76.2 years), and 20 to the L group (mean age 74.4 years). There were no significant differences between the three groups in patient characteristics, concomitant analgesics, or baseline VAS score, gait balance, or QOL-related scores (p ≥ 0.05). The VAS and leg pain scores were significantly improved in Group L, and LBP was improved significantly in Group N. QOL and ODI scores improved significantly in the NL and L groups, EQ-5D score improved significantly in the L group, and RDQ score improved significantly in all groups (p < 0.05). Psychological factor and PCS scores improved significantly in the NL and L groups (p < 0.05). Walking speed and stride length were improved significantly in the NL and N groups (p < 0.05). TUG/FTSST scores were improved significantly in all groups (p < 0.05). Leg pain VAS score was improved significantly (p < 0.05) in the L group compared with the NL group after 6 and 12 weeks of administration, and LBP VAS was improved significantly in the N group after 6 weeks compared with the NL group (p < 0.05). Walking speed was significantly improved in the NL group after 2 weeks compared with the N group and improved significantly in the NL group after 6 weeks (p < 0.05) compared with the L group. RDQ was decreased significantly in the L group compared with the NL group after 8 weeks (p < 0.05). Conclusions Combined use of Neurotropin and limaprost showed an additional effect on walking speed compared with single drug administration. Neurotropin may contribute to the improvement of low back pain, walking speed/stride length, and standing balance. Trial Registration Japan Registry of Clinical Trials (jRCTs031200282).